Arima-Garch models in estimating market risk using value at risk for the WIG20 index - Kamil Makiel (e-Finanse: Financial Internet Quarterly, 2012)
This paper determines whether the VaR estimation is influenced by conditional distribution of return rates (normal, t-student, GED) and attempts to choose the model which best estimates VaR on a selected example. We considered logarithmic return rates for the WIG-20 index from 1999-2011. Then, on their basis we estimates various types of ARIMA-GARCH (1,1) models. Applying relevant models we calculated VaR for the long and short position. The differences between the models were settled on the basis of the Kupiec test.
Keywords: G10; C58; 330; VaR; risk; GARCH